TYPES OF FUNGI ISOLATED FROM SOYBEANS IN THE TASHKENT REGION AND THEIR SYSTEMATIC ANALYSIS (Archive of Conferences, 2021)
This article analyzes fungal diseases of soybeans, their biology, species composition, bioecology and morphology. Sphaerohsidales, Peronosporales, Erysiphales, Hyhomycetales, which are common in the shade, have also been studied.